2005
DOI: 10.1111/j.1651-2227.2005.tb01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being among children and adolescents with mobility impairment in relation to demographic data and disability characteristics

Abstract: These findings increase our limited knowledge of well-being among children/adolescents with mobility impairment and provide a basis for effective care and future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…Our fi nding that pain was associated with poorer QoL on all domains is confi rmed by studies of children with cerebral palsy, 15,16 mobility impairment, 38 and arthritis. 42,43 In our sample, 54% had experienced pain in the previous week, a higher prevalence than in the general population.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our fi nding that pain was associated with poorer QoL on all domains is confi rmed by studies of children with cerebral palsy, 15,16 mobility impairment, 38 and arthritis. 42,43 In our sample, 54% had experienced pain in the previous week, a higher prevalence than in the general population.…”
Section: Discussionsupporting
confidence: 75%
“…15 Studies in disabled children without cerebral palsy had contrasting fi ndings: for example, in children with mobility impairment 38 or spina bifi da 17 severity of impairment was not related to QoL, but in children with arthritis it was. 39 Few studies have compared self-reported QoL of children aged 8-12 years who have cerebral palsy with that of the general population of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…There is a place and a need for both approaches (Stein 1996). It is fair to say that although a substantial research literature is available on older persons acquiring mobility limitations, there is a lack of research on children and adolescents with mobility limitations specifically (Jemtå et al 2005;Alriks-son-Schmidt et al 2007). Clearly, the ramifications of growing up with a mobility limitation are quite different from acquiring them at an older age.…”
Section: Theoretical Perspectivescondition or Function?mentioning
confidence: 96%
“…To predict how any individual child with a mobility limitation will adapt is complicated and complex to say the least. As an example, psychologically, the child with an acquired mobility limitation may respond differently from the child with the mobility limitation from birth in that there may be a sense of loss, grief, and a feeling of lost identity (Jemtå et al 2005) that is, applicable (to the child) with the acquired mobility limitation. Wallander and Varni (1998) outlined in their "Conceptual Model of Adjustment to Pediatric Chronic Physical Disorders" pertinent categories of risk or resistance factors that also have relevance when considering children with a mobility limitation specifically.…”
Section: Theoretical Perspectivescondition or Function?mentioning
confidence: 99%
“…This may hamper participation in everyday life activities, such as with family and at school, and other social events, for children with CP (Beckung & Hagberg, 2002;Jemta, Dahl, Fugl-Meyer, & Stensman, 2005). In addition, they use a large amount of energy in attempts to report the pain, which distracts their attention from the activity at hand (Castle, Imms, & Howie, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%